Reducing the treatment gap for mental, neurological and substance use disorders in Africa: lessons from the Friendship Bench in Zimbabwe. (12th April 2017) - Chibanda, D.
Abstract : Mental, neurological and substance use disorders (MNS) are a leading cause of disability in Africa. In response to the large treatment gap for MNS, a growing body of evidence-based treatments (EBTs) is emerging from Africa; however, there is a dearth of knowledge on how to scale up EBT. The Friendship Bench intervention is a brief psychological treatment delivered through the primary health care system in Zimbabwe by trained lay health workers. It has contributed significantly towards narrowing the treatment gap for common mental disorders in Zimbabwe where it has been scaled up to over 70 primary health care facilities. A three-pronged approach consisting of community engagement, use of EBTs and a government endorsed scale-up plan is described as part of the key strategy leading to the scale up of the Friendship Bench.